Krüppel-like factors in tumors: Key regulators and therapeutic avenues - Zhang, Yuchen; Yao, Chongjie; Ju, Ziyong; Jiao, Danli; Hu, Dan; Qi, Li; Liu, Shimin; Wu, Xueqing; Zhao, Chen (Frontiers in Oncology, 2023)
Krüppel-like factors (KLFs) are a group of DNA-binding transcriptional regulators with multiple essential functions in various cellular processes, including proliferation, migration, inflammation, and angiogenesis. The aberrant expression of KLFs is often found in tumor tissues and is essential for tumor development. At the molecular level, KLFs regulate multiple signaling pathways and mediate crosstalk among them. Some KLFs may also be molecular switches for specific biological signals, driving their transition from tumor suppressors to promoters. At the histological level, the abnormal expression of KLFs is closely associated with tumor cell stemness, proliferation, apoptosis, and alterations in the tumor microenvironment. Notably, the role of each KLF in tumors varies according to tumor type and different stages of tumor development rather than being invariant. In this review, we focus on the advances in the molecular biology of KLFs, particularly the regulations of several classical signaling pathways by these factors, and the critical role of KLFs in tumor development. We also highlight their strong potential as molecular targets in tumor therapy and suggest potential directions for clinical translational research.